2022
DOI: 10.1007/s00704-022-04038-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of land cover change and elevation on decadal trend of land surface temperature: a linear model with sum contrast analysis

Abstract: Land surface temperature (LST) is a significant factor in surface energy balance and global climatology studies. Land cover (LC) and elevation are two factors that affect the change of LST, and their effects depend on different geography. This study aims to demonstrate an alternative approach to examine the change of LST during 20 years (2001 to 2020) on Taiwan Island and to investigate the effect of LC change and elevation on a decadal trend of LST using a linear model that adjusting for each determinate fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The overall mean daytime LST increased by 0.021 • C per decade. This finding is parallel with the previous analysis by Abdulmana et al [22]; Abdulmana et al [23], that Taiwan's daytime LST had increased. Moreover, our findings are consistent with the Council for Economic Planning and Development in Taiwan report [24], which reported that Taiwan's temperature in the years 1980-2009 had increased by 0.29 • C per decade.…”
Section: Discussionsupporting
confidence: 90%
“…The overall mean daytime LST increased by 0.021 • C per decade. This finding is parallel with the previous analysis by Abdulmana et al [22]; Abdulmana et al [23], that Taiwan's daytime LST had increased. Moreover, our findings are consistent with the Council for Economic Planning and Development in Taiwan report [24], which reported that Taiwan's temperature in the years 1980-2009 had increased by 0.29 • C per decade.…”
Section: Discussionsupporting
confidence: 90%
“…Weighted sum contrasts have been commonly utilized in previous studies employing linear and logistic regression models. For instance, utilized weighted sum contrasts in linear regression to evaluate the influence of land-cover transformation and Elevation (EV) on decadal changes in Land Surface Temperature (LST) by comparing the adjusted mean of all factors [27]. Conducted a comparison of blood lead levels among children in the Pattani River region of Thailand [28], while the examined HIV mortality by age group and gender in Thailand between 2014 and 2015 [29].…”
Section: Introductionmentioning
confidence: 99%